Portuguese version of Bern Illegitimates Task Scale: adaptation and evidence of validity - Neves, Paula C. (2023)
Background: A new element for job stress called Illegitimate Tasks has been investigated in recent years, along with stress as an offense to self-theory. Illegitimate tasks are those that are either needless or unrelated to the employee's role and can be categorized as unreasonable tasks and unnecessary tasks. Methods: This study aimed to adapt the Bern Illegitimate Tasks Scale to Portuguese and provide evidence of its validity, through a confirmatory factor analysis with a sample of 472 workers from different sectors. Results: The internal consistency, of the whole scale, measured by Cronbach’s alpha, was 0.923 and 0.902 and 0.928 for the unnecessary tasks and, for unreasonable tasks subscales respectively. The confirmatory analysis supported a two-factor model and showed good to very good indexes of fit (CFI = 0.985; TLI = 0.997; SRMR = 0.035; RMSEA = 0.171). Discussion: The Portuguese version of the Bern Illegitimate Tasks Scale presents very good psychometric properties for the intended measurement goals and can now be used in research with Portuguese speaking samples.